STUDI EVALUASI SEKOLAH RAMAH ANAK DI SDN SERANG 3 - Fadhilah, Jihan; Andriana, Encep; Setiawan, Sigit (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
The aim of this study is to describe the context, input, process, and product aspects of the Child-Friendly School (Sekolah Ramah Anak) program at SDN Serang 3. This research employed an evaluative method using the CIPP model (Context, Input, Process, Product), with a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, while data analysis was performed using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The findings show that SDN Serang 3 has met students' needs by providing a safe and comfortable environment, free from negative behaviors or violence, clean and healthy, and capable of developing students' potentials within the school. The impact of the Child-Friendly School (SRA) program is evident in the areas of children's character, school environment, activities, and habituation.